Patient perceived weight stigma and patient-centered language use preferences: A cross-sectional mixed methods analysis conducted in a large academic medical center - Ryan M. Kane; Selvi B. Williams; Kimberly Reynolds; Abby Kincanon; Marcy R. Hager; Craig McDougall; Jonathan Q. Purnell; Patricia A. Carney (PLoS ONE, 2025)
Background Due to the rising prevalence of obesity and its impact on healthcare, patient-specific context is needed to optimize weight management with an emphasis on reducing health care-associated weight stigma. Our survey aimed to explore institution-specific patient experiences of weight stigma and preferences for patient-centered language use regarding weight management care. Methods This cross-sectional analysis adopted a concurrent mixed methods design with a sample of individuals who opted in to complete patient experience surveys after receiving care at a large academic medical center in the United States (U.S.). Categorical and continuous variables were assessed using Chi-squared and analysis of variance. We used classical content analysis to qualitatively analyze free-text data for thematic coding. Results After a 1-week survey fielding period, 3,219 of 16,758 patients completed the survey, yielding a response rate of (19.2%) with 2,816 having available electronic health record body mass index (BMI) data. Patients were comfortable discussing weight with their primary care providers but showed variation in the preferred approach and terms. Female patients with higher BMIs reported higher rates of delayed and canceled care due to prior weight stigma (25.6% and 12.2% for patients with class 3 obesity), and preferred a slower, gentler, and less direct approach with term preferences for “healthy eating plan” and against “obesity.” Qualitative analysis yielded 27 themes grouped into three domains: Emotional Hinderances, Perceptual Hinderances, and Perceived Helpfulness. Conclusions Findings from our large single institution cohort expand on the existing weight stigma literature by identifying patient language preferences and healthcare experiences according to patient weight class and sex. Given the potential impact of understanding context-specific patient language use preferences to reduce weight stigma, we recommend other healthcare systems use a similar process to address weight stigma as part of a coordinated health system improvement initiative to enhance patient-centered weight management care.